A discovery of witches. Season 2 [videorecording (DVD)] - Goode, Matthew, 1978-; Palmer, Teresa, 1986-; Aird, Holly, 1969-; Bluemel, Edward, 1993-; Harkness, Deborah E., 1965- (Image Entertainment, 2021)
Having escaped to hide in Elizabethan London, Matthew and Diana must find a powerful witch teacher to help Diana control her magic and search for the elusive Book of Life. Enemies are everywhere, the threat to witches is growing, and Diana and Matthew's romance faces a barrage of new threats, from within as much as without.